The The Influence of E-Flash Card Media Towards Students’ Speaking Skill at The Seventh Grade Students of MTs MA Binuangeun Lebak Banten in Academic Year 2021/2022 - Andayani, Nova; Riandi, Riandi; Munawaroh, Tatu (Universitas Mathla'ul Anwar Banten, 2022)
The objective of this research is to find out the significant effect of using e Flash Card media towards students’ speaking skill at the Seventh-grade students of MTs MA Binuangeun Lebak Banten in Academic Year 2021/2022. This research was conducted by using quantitative approach with true experimental method, with experimental and control class. In experimental class, researcher has applied e flash card as a teaching media in teaching while in control class used conventional teaching media. The researcher used pre-test and post-test in both experimental and control class. The data collection techniques used in this research are giving pre-test, treatment, and post-test. The research findings show that e-flash card media is successful applied in the class and all students showed their progress together. Therefore, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. Clearly, the research proved that e-flash card media has significant effect towards students’ speaking skill at the seventh-grade students of MTs MA Binuangeun Lebak Banten in academic year 2021/2022.